Stab wound of superior mesenteric vein and pancreas - Larre Borges, Uruguay; Cassinelli, Daniel; Mesa Figueras, Guillermo (Cirugía del Uruguay, 2021)
The paper gives an account of R clinical observation of a wound in the superior mesenteric vein accompanied by partial section of the pancreas. Sorne urgent therapeutic guidelines for this type of wound are studied and the favourable evolution of the case is shown.